Evaluation of The Implementation of Loading and Unloading Service Standards in the Talang Duku Port Area, Muaro Jambi Regency - Juwita A; Novita Wulandari; M. Abduh (Trescode Green Organization, 2025)
Duku Port, located along the Batanghari River, plays a strategic role as a gateway for international trade in the Jambi region. However, the port faces significant challenges due to the shallow river channel, which limits access for large-tonnage vessels. Only smaller ships can operate safely, while larger vessels must wait for high tide or divert to other ports. This condition reduces the port’s operational performance, decreases revenue, and hinders regional economic growth. Although these issues have been acknowledged, comprehensive evaluations of cargo handling service standards remain limited. This study aims to assess the effectiveness of these service standards through a qualitative case study approach. Data were collected through in-depth interviews, direct observation, and document analysis, followed by descriptive and interpretive analysis. The findings indicate that the implementation of service standards has improved loading and unloading efficiency and reduced operational costs. Nevertheless, technical and service-related limitations persist. Therefore, strengthening infrastructure, conducting regular training, and adopting new technologies are essential. This study highlights the need for continuous evaluation and improvement of service standards to ensure safe and efficient port operations that support international trade and regional economic development.